FAKTOR-FAKTOR YANG MEMPENGARUHI PRODUKSI AYAM BROILER DI KABUPATEN WONOGIRI - Sunarno -; Endang Siti Rahayu; Sutrisno Hadi Purnomo (Universitas Muhammadiyah Semarang, 2017)
This research aimed to determine factors-factors affecting the production of broilers and income levels of broilers and broiler chicken farming efficiency in Wonogiri. The research method is a survey method. The study was conducted in Wonogiri. Sampling with simple random sampling method. The results showed that the correlation factors with broiler production expressed in cobb douglas production function models, namely: LnY = 1.4207 + 0.3312 + 0.2815 LnX1 LnX3 LnX2 + 0.0021 + 0.0080 + 0.0307 LnX4 LnX5 + 0.1732 + 0.1460 LnX6 LnX7 - 0.1081 LnX8 + e. Regression analysis showed that the DOC, feed, labor, vaccines, medicine, vitamins and mortality jointly significant effect on broiler production. Individual factors DOC, feed, vitamins and mortality significantly affect to broilers production, while labor, vaccines and drug did not significantly affect the broilers production. Income levels of broiler chicken farming is Rp. 10.563.345, - perperiode. While the calculation of R/C ratio is 1.06, which means the business of broiler chickens is already profitable. Keywords: Production, Factors affecting, broilers.